Karyotype Analysis of Pisum arvense L. Collected from Tokat Native Vegetation - Yaşar Karadağ (Journal of Agricultural Sciences)
This research was conducted to determine karyotype analysis of Pisum arvense L. occurred in native vegetation of Tokat region After the seeds vvere germinated, they vvere stained by feulgen and karyotype analysis was carrıed out with obtained cells by using the squash method The results of the cytologıcal studıes that the chromosome numbers of Pisum arvense L vvere 2n= 14. Four chromosomes of the Pisum arvense L. were submedian and ten chromosomes vvere median. İn addition, the chromosome length, the arm index and the relatıve chromosome length ın Pisum arvense L. vvere 4.59-5 93 p, 0.56-0.91 and 6.38-8.24, respectively